2015
DOI: 10.1007/s10856-014-5361-7
|View full text |Cite
|
Sign up to set email alerts
|

Elasticity and structure of the compounds in the wollastonite (CaSiO3)–Na2SiO3 system: from amorphous to crystalline state

Abstract: The elastic properties and structure of four potential bioactive compounds in the CaSiO3-Na2SiO3 system were characterized by Raman and Brillouin spectroscopy at ambient conditions. The increase of Na2O content in the Na2O-CaO-SiO2 glass with the same silica content and hence polymerization was found to lower the elastic moduli with accompanied decrease of Q(0) and Q(2) species, increase of Q(1) species and negligible change of Q(3) species, corresponding to a lower and higher equilibrium constant for the disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 41 publications
3
21
0
Order By: Relevance
“…Very similar bands were found for the crystalline phase that was derived from the glass of the CaSiO 3 -Na 2 SiO 3 system with the Na 2 O:CaO:2SiO 2 molar ratio, which was quite close to that occurring in the 45S5 bioglass. In particular, the most intense band at 985 cm −1 can be assigned to Q 2 Si species in the chain or ring crystalline silicates [48]. This suggests that the above-mentioned signals can be attributed to crystalline sodium calcium silicate Na 2 Ca 2 Si 3 O 9 phase (combeite), as identified by the XRD (Fig.…”
Section: Raman Spectroscopymentioning
confidence: 75%
“…Very similar bands were found for the crystalline phase that was derived from the glass of the CaSiO 3 -Na 2 SiO 3 system with the Na 2 O:CaO:2SiO 2 molar ratio, which was quite close to that occurring in the 45S5 bioglass. In particular, the most intense band at 985 cm −1 can be assigned to Q 2 Si species in the chain or ring crystalline silicates [48]. This suggests that the above-mentioned signals can be attributed to crystalline sodium calcium silicate Na 2 Ca 2 Si 3 O 9 phase (combeite), as identified by the XRD (Fig.…”
Section: Raman Spectroscopymentioning
confidence: 75%
“…The latter spectrum is simply characterized by 2 distinct signals, a broader one, corresponding to the amorphous component of the sample, with chemical shifts spanning from −65 to −95 ppm and a narrow feature at approximately ‐83.5 ppm, which is assigned to the presence of pseudowollastonite (α‐Ca 3 Si 3 O 9 ) . The amorphous spectral component of the anhydrous sample has a Q n structural unit distribution typical of calcium metasilicate glasses, ranging from Q 0 to Q 3 groups and a negligible or nonexistent amount of Q 4 units …”
Section: Resultsmentioning
confidence: 99%
“…Anhydrous material powders and the corresponding dried pastes after 28 days of hydration were analyzed by solidstate NMR analysis using a TecMag (Redstone)/Bruker 300 "wide bore" spectrometer with a 7 mm solid-state probe operating at 59.595 MHz for 29 Si observation and at 78.216 MHz for 27 Al observation. Only the samples hydrated for 28 days were chosen for NMR analysis due to the limited time of access to the NMR facilities and because XRD analysis showed that the main phase changes already occurred by 28 days.…”
Section: Al and 29 Si Mas Nmrmentioning
confidence: 99%
See 2 more Smart Citations